Teaching Arabic for cultural purposes: a case study of Francophone program of Arabic at Aleppo University - Jamous, Rawya; Chik, Abdul Rahman (Elsevier, 2012)
This paper aims to shed the light on the program of teaching Arabic to students of French-speaking countries at the University of Aleppo, Syria entitled "teaching of Arabic Language through Orient Culture". The paper will demonstrate the success story of teaching Arabic to non-native speakers by offering a model of a program of teaching Arabic through experiencing Arabic and Islamic culture at their homeland. The study applies the descriptive analytical method, as it displays the activities of the program, analyzes the syllabus and evaluates the program outcomes. Its significance lies on strengthening the language culture.